Juridical analysis of criminal law enforcement of documenters of household violence - Tatang (Journal of Law Science, 2023)
Domestic violence is classified as a special crime, and is the most common case of violence in Indonesia. The focus of the problem in this study is the enforcement of criminal law against perpetrators of domestic violence based on Law Number 23 of 2004 concerning the Elimination of Domestic Violence. The type used is normative juridical research with a statutory approach to further study the legal basis that causes disparities in sentencing of perpetrators of crimes in cases of domestic violence. Law enforcement against criminalizing perpetrators of domestic violence refers to the provisions in Law Number 23 of 2004 concerning the Elimination of Domestic Violence. In fact, law enforcement for criminalizing perpetrators of domestic violence has not been implemented properly, which has resulted in more cases of domestic violence being resolved through mediation. In addition, the disparity in sentencing that occurs is also the cause of the increase in the number of cases of domestic violence, so that the application of sanctions that provide certainty and justice is very important in order to fortify families from all forms of domestic violence